Los inicios de la higiene en Lima Los médicos y la construcción de la higiene - Zárate Cárdenas, Eduardo (2006)
This article analyzes the vicissitudes and difficulties in the construction of discourse and practices of hygiene in Lima in the first half of the twentieth century. This analysis of illnesses deals with a repertoire of practices and imagery that reflect the history of Medicine. In this sense, this work analyzes the discourse of the government and the doctors concerned with the epidemics. We discuss the limits of hygiene illustrated by popular or rural hygiene and the factors that blocked this slow process for several decades. The role played by doctors in the decades of 1840 to 1860 is underlined, as shown by the first publication of La Gaceta Medica de Lima.